Comparative study of efficiency of maxillary canine movement between low friction brackets and conventional brackets in corticotomy-assisted orthodontic patients - Thanawat Kiattawornwong (Prince of Songkla University, 2015)
Thesis (M.Sc. (Oral Health Sciences))--Prince of Songkla University, 2014